PERAN PEMIMPINAN INFORMAL DALAM PEMBANGUNAN DAERAH - Dahlan Husain; Abdurrahman Kader (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2020)
The main focus of this research is the role of informal leadership in regional development. The method used is qualitative by using descriptive, and data obtained using literature study methods of the journals of previous research results in various regions in Indonesia. Data obtained by searching online in Google Scholar database. Research results show that the role of informal leaders in development is needed by local communities, especially those who have a system of cultural values and local wisdom that are still strong. Therefore, areas where there are still communities that have local wisdom in the form of informal leaders can be used as a resource in their regional development